Incidence of lung cancer among healthcare workers in Hunan Province and analysis of related risk factors - Xiao, Jinzhang; Li, Sishi; Zhu, Shudong; Ranjan, Kamakshi; Zhang, Dianzheng (Frontiers in Public Health, 2024)
Background The prevalence of lung cancer, a major type of malignant tumor, has been increasing over the years greatly impacting the health of Chinese residents. This study investigates the epidemiological characteristics of lung cancer among healthcare workers in the Hunan Province, as well as the occupational risk factors. Methods The data analyzed in this study was collected from the largest tumor hospital in the province: the Hunan Provincial Tumor Hospital affiliated with Central South University, School of Medicine. The data collected encompasses input collected between the years of 2004 to 2013 of the population of healthcare workers who were hospitalized for lung cancer treatments. Information was obtained through statistical analysis and telephonic interviews. Results The prevalence of lung cancer among healthcare workers was much higher than that of the general population, as revealed by the difference between number of healthcare worker cases per 1,000 cases and number of healthcare workers per 1,000 population in the decade from 2004 to 2013. Analysis of the data further demonstrates that lung cancer prevalence among healthcare workers increases exponentially with age. Although smoking has been shown to increase the incidence of lung cancer to some extent, it is most likely not the main cause of lung cancer. In addition, it appears that the highest rates of lung cancer incidence occurs in mainly in primary general practitioners, medical radiologists, and nurses. The lack of awareness of personal safety measures may place healthcare workers at a greater risk of lung cancer.